Social Work Students’ Awareness of the Phenomenon of Gender Based Violence - Khalil al-Khaddam , Hamza (Jordan Journal of Social Sciences, 2022)
This study aimed at investigating the awareness level of social work students of the phenomenon of violence based on gender and their attitudes towards it. The study sample consisted of (476) male and female students. The study followed a research methodology relying on the descriptive analytical approach and adopted the questionnaire as a research tool. The study found that the awareness level of social work students of the phenomenon of violence based on gender was positive, with an average of 3.91 and a standard deviation of 0.77. All of the axis were positive, where the “Concept of gender-based violence” and “Forms of gender-based violence” came first, followed by “Role of social work profession in taking care of women subject to violence”, and “Causes of gender-based violence” came last. In addition, the results of statistical analysis showed that there are no statistically significant differences at the level of significance (  0.05) in the students’ awareness level of the phenomenon of violence based on gender which can be attributed to the study variables (gender, family’s educational level , academic level). According to the study results, the study made the following recommendations: - Conducting more research on the awareness of gender-based violence and its effects on other samples and societies employed in the current study. - Conducting a study on the role of the family in social upbringing in the shadow of social, cultural, economic and political changes witnessed by societies from time to time.